Military applications of data analytics - Huggins, Kevin (Data analytics applications, 2019)
The military produces, senses, and consumes a tremendous amount of data. Developing ways to effectively leverage these troves of data to enhance operations is a persistent goal. This book explores data analytics techniques that military scientists and practitioners around the world are doing to achieve this. The book is organized around data analytics applications in the primary military domains of Personnel, Intelligence, Operations, and Logistics.